Implementing Results Based Management in Thailand - World Bank (Washington, DC, 2017)
Thailand has been pursuing the implementation of results based management techniques in the public sector for over a decade. Leading this task is the Office of the Public Sector Development Commission (OPDC) which has been supporting various agencies and departments in undertaking a wide variety of results based management reforms, including key performance indicators, balanced scorecards, and individual performance bonuses, among others. This report summarizes the results of a two week fact finding mission and a one day workshop conducted by the Office of the Public Sector Development Commission (OPDC) of the Prime Minister's office in collaboration with the World Bank's Public Sector Performance Global Expert Team (PSP-GET) held on September 24, 2010 in Bangkok, Thailand. This report covers the main areas to consider in implementing a results based management system. The report provides an overview of Thailand's Results Based Management (RBM) system, with an emphasis on lessons from international experience in leveraging performance information to deliver results. Chapters on how to link performance with planning and budgeting, as well as an overview of incentives to improve performance are included. Each chapter is loosely structured in the following way: issues identified during discussions; relevant lessons from international experiences; and overall recommendations and findings of the PSP-GET.